Energy-Efficient Ion Recovery from Water Using Electro-Driven Membranes: A Comprehensive Critical Review - Oladipo, Akeem Adeyemi; Ahmad, Mehdi (Mdpi, 2025)
Amid concurrent pressures on water and material resources, recovering valuable ions like lithium and nutrients from brines and wastewater is a critical tenet of the circular economy. This review provides a critical assessment of electro-driven membranes (EDMs) as a key technology platform for achieving this goal with high energy efficiency. A comprehensive synthesis and analysis of the current state-of-the-art of core EDM technologies, including electrodialysis (ED) and membrane capacitive deionization (MCDI), is presented, focusing the analysis on the performance metrics of specific energy consumption and ion selectivity. The findings reveal that the optimal EDM technology is highly application-dependent, with MCDI excelling for dilute streams and ED for concentrated ones. While significant advances in monovalent selective membranes have enabled lithium recovery, achieving high selectivity between ions of the same valence (e.g., Li+/Na+) remains a fundamental challenge. Moreover, persistent issues of membrane fouling and scaling continue to inflate energy consumption and represent a major bottleneck for industrial-scale deployment. While EDMs are a vital technology for ion resource recovery, unlocking their full potential requires a dual-pronged approach: advancing materials science to design novel, highly selective membranes, while simultaneously developing intelligently integrated systems to surmount existing performance and economic barriers.
Keywords: ion recovery; resource recovery; electro-driven membranes; electrodialysis; membrane capacitive deionization; energy efficiency; water treatment; circular economy